TEKNIK JOURNALING SEBAGAI STRATEGI COPING STRESS BAGI REMAJA DI GMIT SESAWI OEPURA - Taboy, Maria Lydia Seo; Martha Fiviany Christy Adar; Regitha Arghalya Beeh; Sherryn Trienanda Riwu; Mernon Yerlinda Carlista Mage; R Pasifikus Ch. Wijaya (Universitas Negeri Padang, 2024)
This training aims to increase understanding and direct practice regarding journalingtechniques as stress coping for teenagers. Training was carried out for teenagers at GMIT Sesawi Oepura. The methods in this training are quite varied, including psychoeducation,writing activities, evaluations, and interspersed with ice breaking so that participants do notf eel bored and the training can run smoothly according to expectations. The training wass uccessful because of the positive response from the training participants. Participants are able to follow the training well and actively participate in every activity.